Synthesis of 2-diphenylphosphinoyl-3,5-diaryl-3,4-dihydro-2H-telluropyrans by reaction of chalcones with bis[(diphenylphosphinoyl)methyl]telluride - Silveira, Claudio C. (2010)
The NaH-promoted tandem Michael addition/intramolecular Wittig-Horner reaction of bis[(diphenylphosphinoyl) methyl]telluride with chalcones stereoselectively afforded trans-2-diphenylphosphinoyl-3,5-diaryl-3,4-dihydro- 2H-telluropyran derivatives in 51-72% yield, under mild conditions.